SENP3 in monocytes/macrophages up‐regulates tissue factor and mediates lipopolysaccharide‐induced acute lung injury by enhancing JNK phosphorylation. Issue 10 (31st March 2020) - Chen, Xuelian; Lao, Yimin; Yi, Jing; Yang, Jie; He, Shuangjun; Chen, Yi
Abstract: The mechanisms underlying coagulation abnormalities in sepsis and septic acute lung injury remain unclear. Tissue factor (TF) initiates coagulation; its production can be regulated by reactive oxygen species (ROS); and monocytes/macrophages produce pathological TF during sepsis. The SUMO2/3 protease SENP3 is redox‐sensitive, and SENP3 accumulation in lipopolysaccharide (LPS)‐activated macrophages is ROS‐dependent. To explore whether SENP3 contributes to LPS‐activated coagulation, we used mice with Senp3 conditional knockout (cKO) in myeloid cells. In the model of LPS‐induced sepsis, SENP3 cKO mice exhibited less severe acute lung injury than SENP3 fl/fl mice. SENP3 cKO mice exhibited decreased TF expression in monocytes and alveolar macrophages, with consequently compromised coagulation in their blood and lungs. In vitro results showed that ROS‐induced SENP3 accumulation contributed to LPS‐induced TF expression, which was reduced by JNK inhibitor SP600125. Furthermore, mice injected with LPS following SP600125 (75 mg/kg) treatment showed decreased monocytes/macrophages TF production and alleviated coagulation activation, with less severe lung injury and higher survival rates. Collectively, the results suggest that SENP3 mediates LPS‐induced coagulation activation by up‐regulating monocyte/macrophage TF production in a JNK‐dependent manner. This work provides new insights into ROS regulation of LPS‐activated coagulation and reveals a link between SUMOylation and coagulation.